Samuel Daniel, A Defense of Ryme (1603) : poétique et politique - Christine Sukic (Etudes Epistémè)
Samuel Daniel’s A Defense of Ryme, published in 1603, is an answer to Thomas Campion’s Observations on English Poesie (1602) and advocates the use of rhyme in English poetry as opposed to Campion’s choice of quantitative poetry. But the debate between the two poets also took part at a specific time in English history, the accession of James VI of Scotland to the throne of England. By reading Daniel’s essay closely, we realize that he also had a greater purpose in mind, and that his « defence » was of a political as well as a poetical nature: by defining rhymed poetry as the « natural » poetry of England, he was also defending a nationalistic vision of English literature, and reminding James I that England had a tradition of its own that had to be preserved.